2018
DOI: 10.1007/s00365-018-9415-9
|View full text |Cite
|
Sign up to set email alerts
|

Embeddings and Lebesgue-Type Inequalities for the Greedy Algorithm in Banach Spaces

Abstract: We obtain Lebesgue-type inequalities for the greedy algorithm for arbitrary complete seminormalized biorthogonal systems in Banach spaces. The bounds are given only in terms of the upper democracy functions of the basis and its dual. We also show that these estimates are equivalent to embeddings between the given Banach space and certain discrete weighted Lorentz spaces. Finally, the asymptotic optimality of these inequalities is illustrated in various examples of non necessarily quasi-greedy bases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Delving deeper into the construction of the space, the authors of [22] proved that B e is not a quasi-greedy basis for KT[ 1,q , u]. This result can also be derived from our next general theorem.…”
Section: Banach Envelopesmentioning
confidence: 59%
See 2 more Smart Citations
“…Delving deeper into the construction of the space, the authors of [22] proved that B e is not a quasi-greedy basis for KT[ 1,q , u]. This result can also be derived from our next general theorem.…”
Section: Banach Envelopesmentioning
confidence: 59%
“…The example in [58, §3.3] is the case KT[ 2 ], while KT[ p ], 1 < p < ∞, was later considered in [47]. The case in which X is a Lorentz space was studied in [22]. We will refer to this method for building quasi-Banach spaces as the KT-method.…”
Section: Banach Envelopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost greedy bases enjoy the property of being democratic (see [14,Theorem 3.3]), i.e., there is a sequence (λ m ) ∞ m=1 such that for any finite subset A of N, When a basis B of a Banach space X is almost greedy, the size of the members of the sequence (k m [B, X]) ∞ m=1 is controlled by a slowly growing function to the extent that (see [ [17] and has been given continuity through several papers and authors (see [3,4,8,11,18]).…”
Section: Conditional Bases In Garling Sequence Spacesmentioning
confidence: 99%
“…). In[4, Section 8.2] it is shown that h * l (m) ≈ m. On the other hand, in the same reference it is proved that the dual space X * with the corresponding dual basis B * satisfies h *…”
mentioning
confidence: 99%